Baltrushaitis in Remizov’s: Arabesques and Dreams - Sproģe, Ludmila (Literatūra, 2025)
The article explores the perception of the Lithuanian poet and translator Jurgis Baltrušaitis by the Russian writer Aleksei Remizov. Communication between the two writers was sporadic, and the affinity of their artistic worlds went unnoticed by both contemporaries and later researchers studying their works. However, a series of narratives based on their interpretations of life’s conflicts, their status as writers, as well as motifs of their creative practices (publications in Symbolist journals, translations, the recording of dreams in literary texts) point to an existing lacuna in the study of possible connections between the two artists. Baltrušaitis is intriguing as a character in Remizov’s texts, most often in the form of a ‘dream’, a special genre that resonates with the oneiric themes in the poetic world of Baltrušaitis. Two perspectives emerge in relation with Baltrušaitis as a figure of both Remizov’s lived and artistic reality: the view from within the uncreative routine of literary life, and the view from the space of creative reality, filled with intricate arabesques and dreams, where the ‘happy Baltrušaitis’ dwells.
Keywords: Aleksei Remizov; Jurgis Baltrušaitis; dream; character; creative consciousness